ANALISIS KEPUASAN PENGGUNA SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG) MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) DI PEMERINTAH KABUPATEN BOALEMO - Rasmawati Ika; Frangky Tupamahu; Alter Lasarudin; Khairul Fathan Habie (LPPM Universitas Muhammadiyah Gorontalo, 2026)
This study was conducted to map the level of user satisfaction with the Personnel Information System (SIMPEG) within the Boalemo Regency Government. A quantitative approach was applied, adopting the End User Computing Satisfaction (EUCS) framework. The research instrument, a questionnaire that had undergone validity and reliability testing, was distributed to 31 respondents, active users of the system. Data analysis revealed that, in aggregate, SIMPEG was deemed satisfactory, with an average score of 4.27, categorized as very satisfied. However, evaluation by dimension revealed disparities; the Content dimension recorded the highest score (4.42), while the Timeliness dimension ranked lowest with a score of 4.15 (categorized as satisfied). These findings indicate that although the information content is adequate, the speed of data access and updates remains a barrier. Therefore, the main recommendation focuses on improving system responsiveness to optimize personnel services